COVID-19 vaccines: current and future challenges - Mohammadi, Davood; Ghasemi, Matin; Manouchehrian, Nahid; Zafarmand, Milad; Akbari, Mitra; Boroumand, Amir Bahador (Frontiers in Pharmacology, 2024)
As of December 2020, around 200 vaccine candidates for Coronavirus Disease 2019 are being developed. COVID-19 vaccines have been created on a number of platforms and are still being developed. Nucleic acid (DNA, RNA) vaccines, viral vector vaccines, inactivated vaccines, protein subunit vaccines, and live attenuated vaccines are among the COVID-19 vaccine modalitiesamong the COVID-19 vaccine possibilities. At this time, at least 52 candidate vaccines at least 52 candidate vaccinations are being studied. Spike protein is the primary protein that COVID-19 vaccines are targeting. Therefore, it is critical to determine whether immunizations provide fullcomplete or partialfractional protection, whether this varies with age, whether vaccinated people are protected from reoccurring diseases, and whether they need booster shots if they've already been inoculated. Despite the enormous achievement of bringing several vaccine candidates to market in less than a year, acquiring herd immunity at the national level and much more so at the global level remains a major challenge. Therefore, we gathered information on the mechanism of action of presently available COVID-19 vaccines in this review and essential data on the vaccines' advantages and downsides and their future possibilities.